2014
DOI: 10.1002/ajoc.201402211
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Acceleration of a Photochemical Replicator

Abstract: The photoinduced decarbonylation of an a-diketone adduct generates 2,6-dimethoxyanthracene in the ground state. The photochemical product can also absorb the incoming photons and transfer its excitation energy to another molecule of the reactant to establish an autocatalytic loop. In the presence of silver nanoparticles, the efficiency of energy transfer increases significantly with a concomitant acceleration of the autocatalytic transformation. In principle, this mechanism to establish kinetic amplification c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…It should be noted that the onset of self-catalysis means that the rate of bleaching takes on a significant time dependence. It should be emphasized that there are other examples of photochemical self-catalyzed reactions in the literature. These reactions cover a variety of systems where light promotes unusual chemistry but nonetheless the range of photochemical self-catalyzed processes remains relatively small.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the onset of self-catalysis means that the rate of bleaching takes on a significant time dependence. It should be emphasized that there are other examples of photochemical self-catalyzed reactions in the literature. These reactions cover a variety of systems where light promotes unusual chemistry but nonetheless the range of photochemical self-catalyzed processes remains relatively small.…”
Section: Discussionmentioning
confidence: 99%
“…[24] Early examples of photoactivatable fluorophores were based on the covalent attachment of photocleavable ortho-nitrobenzyl groups to fluorescein. [25][26][27] Similar structural designs were later adapted to photoactivate also the fluorescence of anthracene, [28][29][30][31][32][33][34][35][36] resorufin, [37] rhodamine, pyrene, [60] coumarin, [61][62][63][64][65][66] dihydrofurans, [67][68][69][70][71][72] acridinone, [73][74][75] and thiocarbonyl [76] derivatives. In most of these photoresponsive compounds, fluorescence switching is a result of a change in either the rate of nonradiative deactivation of the excited fluorophore or its molar absorption coefficient at the excitation wavelength (λ Ex ).…”
Section: Photoactivatable Fluorophoresmentioning
confidence: 99%
“…This fundamental phenomenon was termed photofluorescence almost five decades ago, but its potential biological implications were only recognized much later in seminal reports on photocaged fluoresceins. These investigations demonstrated that the photoinduced disconnection of appropriate functional groups from organic chromophores can be exploited to convert a nonemissive reactant into an emissive product (panel a in Figure ). In the wake of these pioneering contributions, similar operating principles to photoactivate fluorescence were extended to a diversity of emissive chromophores, including anthracene, resorufin, rhodamine, pyrene, coumarin, dihydrofurans, acridinone, borondipyrromethene (BODIPY), and thiocarbonyl derivatives. In all instances, irradiation at λ Ac activates the photochemical conversion of reactant into product and illumination at λ Ex excites the latter species to produce fluorescence.…”
Section: Synthetic Photoactivatable Fluorophores For Live-cell Imagingmentioning
confidence: 99%